Semantic web support for open-source software development - Dillon, Tharam S.; Simmons, Gregory (Institute of Electrical and Electronics Engineers (IEEE) Computer Society, 2008)
Open-source software is unique in that the development of the product is performed in public over the Internet by developers who elect to contribute to the project and rarely if ever meet face-to-face. Software development is a knowledge intensive process and the information generated in open-source software development projects is typically housed in a central Internet repository. Open-source repositories typically contains vast amounts of information, much of it unstructured, meaning that even if a question has previously been discussed and dealt with it is not a trivial task to locate it, leading to rework, confusion amongst developers and possibly deterring new developers from getting involved.This paper develops an ontology based software development architecture for open-source software development. Such an architecture would enable better categorisation of information, communication, co-ordination and the development of sophisticated search agents.